Farming of Plant-Based Veterinary Vaccines and Their Applications for Disease Prevention in Animals - Pit Sze Liew; Mohd Hair-Bejo (Advances in Virology)
Plants have been studied for the production of pharmaceutical compounds for more than two decades now. Ever since the plant-made poultry vaccine against Newcastle disease virus made a breakthrough and went all the way to obtain regulatory approval, research to use plants for expression and delivery of vaccine proteins for animals was intensified. Indeed, in view of the high production costs of veterinary vaccines, plants represent attractive biofactories and offer many promising advantages in the production of recombinant vaccine proteins. Furthermore, the possibility of conducting immunogenicity and challenge studies in target animals has greatly exaggerated the progress. Although there are no edible plant-produced animal vaccines in the market, plant-based vaccine technology has great potentials. In this review, development, uses, and advantages of plant-based recombinant protein production in various expression platforms are discussed. In addition, examples of plant-based veterinary vaccines showing strong indication in terms of efficacy in animal disease prevention are also described.